Determination of relevant mechanical properties for the production process of polyethylene by using mesoscale molecular simulation techniques. Issue 2 (2nd July 2020) - Grommes, Dirk; Reith, Dirk
ABSTRACT: In this study, we determine the strain rate and temperature-dependent mechanical material behavior as well as the glass transition temperature and coefficient of thermal expansion of polyethylene melts using molecular dynamics simulation. In order to achieve realistic chain lengths polyethylene was simulated by three different coarse-grained models of various bead sizes. All simulations are performed by using the simulation package ESPResSo++, which we extended with a regulation procedure for the simulation of tensile tests on the micro-scale. The process-relevant observables, such as the elastic modulus, yield stress, and Poisson's ratio are investigated at the meso-level. The chain orientation and entanglement behavior show effects that precisely illuminate the experimental stress strain response, giving important hints for production process control. Summarized, we are able to successfully reproduce the characteristic stress strain response for polyethylene as observed in experiments. Thus, we establish a closer link between microscopic and macroscopic system descriptions in order to provide a deeper understanding of material properties in their production process, i.e. for changing external conditions.